2015
DOI: 10.1186/s12885-015-1059-6
|View full text |Cite
|
Sign up to set email alerts
|

Co-expression of S100A14 and S100A16 correlates with a poor prognosis in human breast cancer and promotes cancer cell invasion

Abstract: BackgroundS100 family proteins have recently been identified as biomarkers in various cancers. Of this protein family, S100A14 and S100A16 are also believed to play an important role in tumor progression. The aim of the present study was to clarify the clinical significance and functional role of these molecules in breast cancer.MethodsIn a clinical study, an immunohistochemical analysis of S100A14 and S100A16 expression in archival specimens of primary tumors of 167 breast cancer patients was performed. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
47
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 27 publications
5
47
1
Order By: Relevance
“…This member of the S100 protein family has been reported to be involved and overexpressed in several pathological affections, including cancer, but with different and often contradictory roles [119][120][121]. In our tumor tissues we found a single form of S10AG with a 3x fold increase versus the normal tissues.…”
Section: S10ag (S100a16)mentioning
confidence: 49%
“…This member of the S100 protein family has been reported to be involved and overexpressed in several pathological affections, including cancer, but with different and often contradictory roles [119][120][121]. In our tumor tissues we found a single form of S10AG with a 3x fold increase versus the normal tissues.…”
Section: S10ag (S100a16)mentioning
confidence: 49%
“…There are no reports on the expression of S100A16 in cervical carcinoma. It has been reported that a high S100A16 expression level is correlated to poor prognosis in breast cancer and lung adenocarcinoma (27,28), whereas a low S100A16 expression level is correlated with reduced survival and poor tumor differentiation in oral squamous cell carcinoma (29). Further studies are needed to clarify the function of S100A16 and its clinical significance in the various cancer types.…”
Section: Discussionmentioning
confidence: 99%
“…In most cases, absent or faint cytoplasmic staining and no nuclear staining were observed. S100A14 expression was found to be mainly localized in the cytoplasm in ovarian cancer [13], in the cytoplasm and nucleus in hepatocellular carcinoma [14], and on the cell membrane in breast cancer [23]. These different staining patterns suggest that S100A14 localization and function are different in organ-specific cancers.…”
Section: Discussionmentioning
confidence: 97%
“…The breast cancer staining pattern (mainly cell membrane) is similar to lung adenocarcinoma. Tanaka et al [23] reported that in the breast cancer cell lines, S100A14 expression on the membrane along the lateral cell surface was due to interaction and binding with actin; therefore, S100A14 may promote cancer cell migration and invasion. However, interaction between S100A14 and actin in lung adenocarcinoma is unknown, and further analysis is needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation